Fenestration and dehiscence in the alveolar bone of anterior maxillary and mandibular teeth in cone-beam computed tomography of an Iranian population - Zahra Dalili Kajan; Seyed Ebrahim Seyed Monir; Negar Khosravifard; Delara Jahri (Wolters Kluwer Medknow Publications, 2020)
Background: The presence of dentoalveolar lesions such as fenestration and dehiscence has great clinical importance. This study was designed to determine the incidence of bony fenestrations and dehiscences associated with the anterior teeth by using cone-beam computed tomography images. Materials and Methods: A total of 216 images (1189 teeth) were included in this cross-sectional study. The presence of fenestration and dehiscence at the buccal and lingual/palatal surfaces and also their relative levels on the roots of the teeth were determined. McNemar's, Chi-square, and Cochran's Q tests were used for data analysis. A value of P < 0.05 was considered to be statistically significant. Results: The incidence of fenestration and dehiscence was 17.6% and 3.9%, respectively with the maxillary fenestrations being more prevalent (P < 0.0001). No significant differences were observed in the incidence of dehiscences between the jaws (P = 0.824) and among the tooth types (P = 0.689). The lesions were more frequent at the buccal surfaces (80%-92.5%). About 85.9% of the fenestrations occurred in the apical root thirds, whereas dehiscences had the highest prevalence in the cervical thirds. Fenestration and dehiscence incidences were significantly higher in females (P < 0.05). There was no significant difference among the age groups regarding these lesions. Conclusion: Fenestration and dehiscence were observed more on the buccal surfaces and also in the apical and cervical root thirds, respectively. Age had no significant influence on the occurrence of these lesions in contrast to the sex.